2003
DOI: 10.1007/s00427-003-0345-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two T-box genes from sponges, the phylogenetically oldest metazoan taxon

Abstract: It is now well established that all metazoan phyla derived from one common ancestor, the hypothetical Urmetazoa. Due to the basal position of Porifera (Demospongiae) in the phylogenetic tree of Metazoa, studies on the mechanisms controlling the development of these animals can provide clues on the understanding of the origin of multicellular animals and on how the first organization of the body plan evolved. In this report we describe the isolation and genomic characterization of two T-box genes from the silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
63
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 77 publications
4
63
0
Order By: Relevance
“…S1). This result supports the notion that Brachyury is the most ancient member of the T-box family (11,13). Moreover, fungal, and especially filasterean, Brachyury genes have most of the T-box key DNA-binding and dimerization amino acids, as well as conserved exclusive amino acid motifs of the Brachyury class (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…S1). This result supports the notion that Brachyury is the most ancient member of the T-box family (11,13). Moreover, fungal, and especially filasterean, Brachyury genes have most of the T-box key DNA-binding and dimerization amino acids, as well as conserved exclusive amino acid motifs of the Brachyury class (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Previous studies have identified T-box genes in nonbilaterian metazoans (11)(12)(13)(14). This knowledge has enabled a reconstruction of the Urmetazoan T-box complement, which putatively included three classes (Tbx4/5, Brachyury, and a putative Tbx1/15/20), with other classes being added in a stepwise manner through the evolution of metazoans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This toolkit has been suggested to be based on genes required for signaling and regulation (44) and, more specifically, homeotic genes (45,46), which direct the building of multicellular bodies according to a master plan through genetic regulation. We propose an expanded developmental toolkit that includes alternative splicing, acting especially on genes encoding for intrinsically disordered proteins, which, as we have shown, are predominantly involved in signaling and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…We propose an expanded developmental toolkit that includes alternative splicing, acting especially on genes encoding for intrinsically disordered proteins, which, as we have shown, are predominantly involved in signaling and regulation. Indeed, developmental regulation genes have been shown to generate isoforms through alternative splicing: In a particular example, a T-box gene of a sponge, considered the earliest example of metazoans, has been shown to produce isoforms through alternative splicing that affect phosphorylation and glycosylation states, which, in turn, affect gene regulation (46). The combination of these mechanisms also could have facilitated explosive speciation events in the evolutionary history of multicellular organisms, by tolerating multiple mutations that led to changes in regulation and in signaling networks.…”
Section: Discussionmentioning
confidence: 99%